Rhus coriaria (Sumac) induces autophagic cell death and inhibits mTOR, p38MAPK and STAT3 pathways in 5fluorouracil-resistant colorectal cancer cells - Nizami, Zohra Nausheen; Al Azzani, Mazoun; Khaldi, Samah; Wali, Adil Farooq; Magramane, Rym; Samad, Shamaa Abdul; Eid, Ali H.; Arafat, Kholoud; Al Dhaheri, Yusra; Attoub, Samir; Iratni, Rabah (Frontiers in Pharmacology, 2025)
IntroductionColorectal cancer is a leading cause of cancer related-death worldwide, and resistance to 5-fluorouracil (5FU, a key component of chemotherapy regimens, is a major clinical concern. We have previously elucidated the effects of Rhus coriaria ethanolic extract (RCE) in triple-negative breast cancer, CRC, and pancreatic cancer cells. Here, we explored the anticancer effects of RCE in parental (HCT-116-WT) and 5FU-resistant HCT-116 (HCT-116-5FU-R) CRC cells.MethodsMTT assay was used to assess cell viability. Muse analyzer was used to assess cell viability, cell cycle distribution, and apoptosis. Additionally, colony formation and growth assays and western blots were performed. In vivo effects of RCE were assessed by an in ovo chick embryo tumor growth assay.ResultsWe found that RCE inhibited the viability and colony formation and growth capacities of HCT-116-WT and HCT-116-5FU-R cells. The antiproliferative effects were attributed to DNA damage-mediated impairment of cell cycle at S phase, and induction of Beclin-1-independent autophagy in both cell lines. Mechanistically, inhibition of the mTOR, STAT3 and p38 MAPK pathways was implicated in the latter. Additionally, RCE induced caspase-7-independent apoptosis in HCT-116-WT cells. However, HCT-116-5FU-R cells were resistant to apoptosis through upregulation of survivin, and downregulation of Bax. Using autophagy and proteasome inhibitors, we clarified that autophagy and the proteasome pathway contributed to RCE-mediated cell death in HCT-116-WT and HCT-116-5FU-R cells. Lastly, we confirmed RCE inhibited the growth of both HCT-116-WT and HCT-116-5FU-R xenografts in a chick embryo model.DiscussionCollectively, our findings highlight that RCE is a source of phytochemicals that can be used as anticancer agents for 5FU-resistant CRC.